Molecular Traffic Control in a 3D network of single file channels and fast reactivity - Brzank, Andreas; Kwon, Sungchul; Schütz, Gunter (Diffusion Fundamentals, 2005)
We study the conditions for reactivity enhancement of catalytic processes in porous solids by use of molecular traffic control (MTC) as a function of grain size. We extend a recently introduced two dimensional model system to three dimensions. With dynamic Monte-Carlo simulations and analytical solution of the associated Master equation we obtain a quantitative description of the MTC effect in the limit of fast reactivity. The efficiency ratio (compared with a topologically and structurally similar reference system without MTC) is inversely proportional to the grain diameter.